THE USE OF ANATOMIC TABLE FOR STUDYING THE VARIANT ANATOMY OF THE SUBCLAVIAN AND AXILLARY ARTERIES - O.V. MURASHOV (Avicenna Tajik State Medical University, 2020)
Objective: To study of the variant anatomy of the subclavian and axillary arteries and compare the obtained data with the classical anatomy of Russian and foreign anatomical schools. Methods: A study was carried out on the subclavian and axillary arteries of two male and two female dead bodies (Caucasian and Asian) that have been implemented on the basis of the anatomy table «Anatomage Table EDU 6.0.2» - the modern advanced system of visualization in anatomy. The study used the property of the anatomical table to trace the course and determine the diameter of arterial vessels to obtain a 3D image of the entire arterial system or part of it in the studied area of the body. The screenshots have been taken after extracting the arteries of the indicated area and their coloration. A comparison of screenshots with images of classical anatomy of atlases and monographs was carried out visually by the author. Results: The obtained graphic figures allowed to detect the individual features of the subclavian and axillary arteries, including the different arterial branches, their quantity, and order of branching off from the main trunk. Thus, the number of branches of the subclavian artery can count from four to six, and the axillary artery - from three to six. It was established that the branches of the subclavian artery might be the suprascapular, the supreme intercostal and mediastinal arteries, and the posterior humeral circumflex artery can branch off from the anterior humeral circumflex artery or begins with a common trunk from the infrascapular artery. Conclusion: These data should be taken into account in conducting angiographic investigations, surgical interventions, and medical manipulations. Before the surgical intervention, it is necessary to identify the individual characteristics of these arteries at the patient, so that they significantly may affect the medical tactics of the disease and current outcome of upper limb ischemia. A thorough examination of the patient will reveal such features and thus, avoid possible errors and complications during the treatment.